I simboli e le icone di appartenenza religiosa nello spazio pubblico europeo - Cantaro, Antonio (Cultura giuridica e diritto vivente, 2020)
[The symbols and icons of religious affiliation in the European public space] The belief that freedom of religion in all its forms belongs to the universe of fundamental rights is consolidated in the European legal science. Article 3 of the Italian Constitution establishes the equality of citizens before the law and expressly mentions the religious element among the parameters of non-discrimination. Equally strong, regarding the breadth of the content of religious freedom, are the formulations contained in European law. Nevertheless, the European Court of Justice, in some of its recent decisions, has reached conclusions which are likely to downsize the fundamentality of the right to religious freedom, its absoluteness, in the face of the cultural challenges posed by the current immigration, also relating to women’s clothing.